Assessing the Vulnerability of Structures and Residential Communities to Storm Surge: An Analysis of Flood Impact during Hurricane Sandy - Hatzikyriakou, Adam; Lin, Ning (Frontiers in Built Environment, 2018)
With 6.5 million households in the United States located in areas prone to storm surge, assessing the vulnerability of structures and residential communities to coastal flooding is an important concern. Of particular interest is understanding how the performance of structures during surge events is influenced by flood conditions, coastal defenses and building design at both the house and community level. This study presents such a vulnerability analysis by investigating the impact of coastal flooding from Hurricane Sandy (2012) on 95 kilometers of developed coastline across New Jersey and New York. Exterior structural damage observed from a Federal Emergency Management Agency (FEMA) aerial survey of the study area is related to (1) a hindcast simulation of flood inundation and wave action, (2) a classification of coastal defenses and storm-induced erosion, and (3) minimum building design elevations specified in FEMA’s flood hazard mapping. Findings indicate that the hardest hit communities experienced significant dune erosion, which coincided with severe flood and wave exposure. Furthermore, structures were considerably more susceptible to flood impact if Sandy’s flood level exceeded FEMA’s 100-year Base Flood Elevation dictating building design. These results are quantified by developing fragility curves relating both house and community level performance to the considered vulnerability parameters. Findings from this study can be used to inform decision making for improving coastal resilience.